Ten proposed measures to improve vaccination: Health care providers’ perspectives on promoting the vaccination intake of children with special healthcare needs in China - Xiang Guo; Tianxing Feng; Meiyi Chen; Xuran Zhao; Xiangshi Wang; Yanling Ge; Zhonglin Wang; Zhuoying Huang; Mei Zeng (BMJ Paediatrics Open)
Introduction Children with special healthcare needs (CSHCN) often experience vaccination delays or missed vaccines in China. The coverage rate of the age-appropriate National Immunisation Programme vaccine was suboptimal. This study aimed to explore attitudes, behaviours, and suggestions regarding the improvement of routine vaccination services for CSHCN among healthcare providers.Methods This study conducted local, cross-sectional interviews involving vaccination services for CSHCN. A purposive sampling strategy was used to recruit interviewees including primary care providers, paediatricians and immunisation programme administrators. The interview guide explored attitudes towards and suggestions for establishing immunisation advisory clinics and referral networks, updating immunisation guidance documents and vaccine package inserts and strengthening the education of vaccination providers.Results 21 representative healthcare providers were interviewed. 10 measures were proposed to promote routine immunisation for children with special needs: (1) using immunisation advisory clinics to provide vaccination services for CSHCN; (2) establishing a referral network and specifying which cases necessitate referral to advisory clinics; (3) using an interconnected information system to identify, document and follow-up the CSHCN; (4) supporting high-quality clinical research to update immunisation protocols; (5) providing clear and definite immunisation recommendations to parents of eligible CSHCN; (6) seeking immunisation advice from specialised professionals to enhance primary care capability; (7) creating quality improvement programmes; (8) considering immunisation status a mandatory assessment during specialist visits; (9) supporting off-label use of vaccines legally and (10) encouraging pharmaceutical companies to update vaccine package inserts.Conclusion Vaccine uptake among CSHCN in China is suboptimal, highlighting the need for a referral network and a standard immunisation protocol. The National Immunisation Programme should develop clear recommendations and an education programme for regional Centers for Disease Control and Prevention to train local providers. A quality assurance and improvement programme, along with regular feedback, is essential to ensure CSHCN receive necessary vaccinations and protection against infectious diseases.